Análisis de contenido del canal Ëlrubiusomg determinando su influencia con relación a sus seguidores - Carbo García, Ángel Mauricio (2020)
YouTube is a digital platform, or rather known as the most widely used Social Network worldwide, since in it we can find a number of videos of all tastes and preferences. In which videos that have been uploaded by people, who manage their own channels within this platform, are shown. Nowadays, being YouTuber has become one of the most feasible strategies to become known globally through the digital world. These people generate content either on a daily, weekly or monthly basis, however, for the production of their videos, people seek strategies so that their content is entertaining and above all pleasant for the audience or subscribers who in one way or another visit these. pages with the aim of knowing the talent that those people have. The objective of this study is to determine the type of content handled by YouTuber ELRUBIUSOMG through qualitative research, it was allowed to analyze the different parameters that they wanted to determine in order to have a result on the topics that they wanted to analyze.